Craniosynostosis and radial ray defect: A rare presentation of 22q11.2 deletion syndrome. Issue 8 (27th June 2013) - Rojnueangnit, Kitiwan; Robin, Nathaniel H.
Abstract A newborn with bilateral coronal craniosynostosis, hypoplastic thumbs, imperforate anus, and prenatal growth restriction was evaluated and given the clinical diagnosis of Baller–Gerold syndrome (BGS). While confirmatory testing of RECQL4 was pending, the infant developed unexplained hypocalcemia, prompting testing for a 22q11.2 deletion. Subsequently, the infant was found to have a 22q11.2 deletion, and was negative for an RECQL4 mutation. We therefore conclude that 22q11.2 deletion syndrome can present with findings resembling the BGS phenotype. © 2013 Wiley Periodicals, Inc.